Identification of a small molecule HIV-1 inhibitor that targets the capsid hexamer. Issue 3 (1st February 2016) - Xu, Jimmy P.; Branson, Jeffrey D.; Lawrence, Rae; Cocklin, Simon
Graphical abstract: Abstract: The HIV-1 CA protein is an attractive therapeutic target for the development of new antivirals. An inter-protomer pocket within the hexamer configuration of the CA, which is a binding site for key host dependency factors, is an especially appealing region for small molecule targeting. Using a field-based pharmacophore derived from an inhibitor known to interact with this region, coupled to biochemical and biological assessment, we have identified a new compound that inhibits HIV-1 infection and that targets the assembled CA hexamer.